Changing air pollution scenario during COVID-19: Redefining the hotspot regions over India. (15th February 2021) - Tyagi, Bhishma; Choudhury, Goutam; Vissa, Naresh Krishna; Singh, Jyotsna; Tesche, Matthias
Abstract: The present study investigates the air pollution pattern over India during the COVID-19 lockdown period (24 March–31 May 2020), pre-lockdown (1–23 March 2020) and the same periods from 2019 using Moderate Resolution Imaging Spectroradiometer (MODIS) Terra aerosol optical depth (AOD) with level 2 (10 km × 10 km) and level 3 (1° × 1° gridded) collection 6.1 Dark Target Deep Blue (DT-DB) aerosol product the Tropospheric Monitoring Instrument (TROPOMI) NO2 and SO2 data with a spatial resolution of 7 km × 3.5 km. We also use long-term average (2000–2017) of AOD for March–May to identify existing hotspot regions and to compare the variations observed in 2019 and 2020. The aim of the present work is to identify the pollution hotspot regions in India that existed during the lockdown and understanding the future projection scenarios reported by previous studies in light of the present findings. We have incorporated Menn-Kendall trend analysis to understand the AOD trends over India and percentage change in AOD, NO2 and SO2 to identify air pollution pattern changes during the lockdown. The results indicate higher air pollution levels over eastern India over the coal-fired power plants clusters. By considering the earlier projected studies, our results suggest that eastern India will have higher levels of air pollution, making it a new hotspot region for air pollution with highest magnitudes. Graphical abstract: Image 1 Highlights: During the lockdown period, the Indo-Gangetic plain does not appear as a pollution hotspot. AOD values over eastern, central, and western India were high during the lockdown. Eastern India emerged as a strong emission source of NO2 and SO2 during lockdown. The hotspots regions of NO2 and SO2 emission in eastern India are related to coal mining and coal-fired power plants. Abstract : Capsule: The work identifies eastern India as hotspot pollution zone during COVID-19 lockdown. The current results combined with earlier future projections shows eastern India will be the highest pollution region over the Indian region.